Advances in Gene Therapy for Neurologic Disorders: An Overview - Pallavi Chand; K. Trideva Sastri; Ashish Singh Chauhan; Souvik Chakraborty; Vikash Jakhmola (BIO Integration)
Neurologic disorders currently affect approximately 100 million people worldwide. Neurologic disorders most often occur due to inherent genetic mutations, which lead to numerous types of functional disruptions in nervous system development. Neurologic disease-related events, such as genetic and epigenetic changes, cause inflammatory processes in the area which may enhance the disease cycle. Gene therapy has progressed to a compelling therapeutic approach for various neurodegenerative disorders. Several efforts to enhance gene therapy rely on discovering novel vectors, recent curative targets, and the dependability of transgenic delivery paths. These viral and non-viral vectors techniques are carefully screened through preclinical and clinical levels and eventually render patients with effective therapies. This review addresses gene therapy developments and obstacles for neurodegenerative diseases and discusses emerging strategies, goals, and prospects.